2019
DOI: 10.3389/feduc.2018.00116
|View full text |Cite
|
Sign up to set email alerts
|

Automated Feedback Can Improve Hypothesis Quality

Abstract: Stating a hypothesis is one of the central processes in inquiry learning, and often forms the starting point of the inquiry process. We designed, implemented, and evaluated an automated parsing and feedback system that informed students about the quality of hypotheses they had created in an online tool, the hypothesis scratchpad. In two pilot studies in different domains ("supply and demand" from economics and "electrical circuits" from physics) we determined the parser's accuracy by comparing its judgments wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The control condition included the concept mapping tool without feedback, whereas the experimental condition included a version of the concept mapping tool with feedback. In earlier work [35], we found that roughly half of students who had feedback available chose not to use it. We therefore assigned roughly two-thirds of students to the experimental condition, with the expectation that about half of all students in the experimental condition would actually use feedback.…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations
“…The control condition included the concept mapping tool without feedback, whereas the experimental condition included a version of the concept mapping tool with feedback. In earlier work [35], we found that roughly half of students who had feedback available chose not to use it. We therefore assigned roughly two-thirds of students to the experimental condition, with the expectation that about half of all students in the experimental condition would actually use feedback.…”
Section: Methodsmentioning
confidence: 87%
“…The roughly equal distribution of students across these three groups shown in Table I shows that this approach was successful. In previous work [35], we found that letting students explore in a similar learning environment on their own took too much time, and some instruction on how to use the environment was needed. Students were therefore given an oral description of the apps, labs, and resources available to them in the learning environment at the beginning of each phase, and directed to wait for further instructions after completion of each phase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To that end, this paper proposes the first mechanism for describing and transforming visual analytics hypotheses into scientific hypotheses. Drawing from prior work in science and education literature [22,37,58], we propose a grammar for expressing hypothesisbased analytic questions. We start with a grammar that expresses a scientific hypothesis-a specific, narrow, and testable question-and relax it to express sets of scientific hypotheses.…”
Section: Introductionmentioning
confidence: 99%